2013
DOI: 10.1371/journal.pone.0065434
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-Beta Inhibition Reduces Progression of Early Choroidal Neovascularization Lesions in Rats: P17 and P144 Peptides

Abstract: The purpose of this study was to assess the effects of transforming growth factor beta (TGF-β) inhibitor peptides (P17 & P144) on early laser-induced choroidal neovascularization (LI-CNV) lesions in rats, two weeks after laser CNV induction. Seventy-one Long Evans rats underwent diode laser application in an established LI-CNV model. Baseline fluorescein angiography (FA) was performed 14 days following laser procedure, and treatments were administered 16 days post-laser application via different administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…However, injection of anti-TGF-β and anti-TGF-βRI antibodies inhibits chronic synovial inflammation in rats with SCW-induced arthritis [38] and in CAIA mice [25]. In CIA, treatment with p17 TGF-β antagonist at the same doses shown previously to block activity of TGF-β in vivo [31,[39][40][41][42][43] did not prevent or modify the severity of the disease, neither during the induction phase nor during established arthritis. As Marinova-Mutafchieva et al have shown that TGF-β expression is induced in the joints at the time of arthritis onset, the time of treatment of CIA mice during clinical progression of disease is justified.…”
Section: Discussionmentioning
confidence: 86%
“…However, injection of anti-TGF-β and anti-TGF-βRI antibodies inhibits chronic synovial inflammation in rats with SCW-induced arthritis [38] and in CAIA mice [25]. In CIA, treatment with p17 TGF-β antagonist at the same doses shown previously to block activity of TGF-β in vivo [31,[39][40][41][42][43] did not prevent or modify the severity of the disease, neither during the induction phase nor during established arthritis. As Marinova-Mutafchieva et al have shown that TGF-β expression is induced in the joints at the time of arthritis onset, the time of treatment of CIA mice during clinical progression of disease is justified.…”
Section: Discussionmentioning
confidence: 86%
“…Nagineni et al [30] demonstrated that TGF-β can induce the secretion of VEGF from the retinal pigment epithelium (RPE) and choroidal cells, and play an important role in CNV in AMD. Two weeks after laser-induced CNV in rats, Zarranz-Ventura et al [31] confirmed that inhibition of TGF-β can reduce the progression of CNV lesions, and Recalde et al [32] drew a similar conclusion. Yuan and Neufeld [38] found that whereas microglial cells do not express TGF-β 2 in normal optic nerve heads and rarely contain TGF-β 1 , they can express TGF-β 2 in glaucomatous optic nerve heads, and a few of them contain TGF-β 1 .…”
Section: Discussionmentioning
confidence: 88%
“…53,54 These peptides have shown an antagonist effect over TGFb-dependent processes in cellular cultures and a strong TGF-b inhibitory effect in different animal models. 23,[55][56][57] PD Fluid Exposure Model in Mice Female C57BL/6 mice between 12 and 16 weeks of age were used in this study (Harlan Interfauna Iberica, Barcelona, Spain). The experimental protocol used was in accordance with the National Institutes of Health Guide for Care and Use of Laboratory Animals and approved by the Animal Ethics Committee of the Centro de Biología Molecular "Severo Ochoa."…”
Section: Reagentsmentioning
confidence: 99%